A History of the United Nations - Luard, Evan. author. aut Link
VII, 568 p.
Keywords: This is the second volume of the first full-scale history of the United Nations. This volume deals with a period when the organization was involved with major crises over Suez, Hungary, Lebanon and India, the Congo, the Cuba Missile crisis and armed conflicts in West Irian, Yeman, Cyprus, Kashmir and the Dominican Republic. It covers the first four UN peace-keeping operations: in Sinai, the Congo, West Irian and Cyprus.